Pemanfaatan Media Sosial Sebagai Media Promosi Produk UMKM di Sumatera Barat - Nitasri Murawaty Girsang; Wahyu Nova Riski (Institut Seni Indonesia Padangpanjang, 2023)
The development of communication technology has a significant influence on promotional media and marketing activities. Social media is one of the popular media and is considered effective in supporting the marketing of UMKM products. This study aims to look at the forms of social media use in the process of marketing UMKM products in West Sumatra. Using qualitative methods and a descriptive approach, the results of this study show that the forms of social media use vary from one UMKM to another. There are UMKM that consistently carry out direct selling and lose opportunities to build interaction with consumers. On the other hand, there are UMKM that have successfully marketed their products while building interactive relationships with their consumers by utilizing the features and facilities provided by social media platforms. This research adds to the academic corpus related to the use of social media for marketing MSME products at the regional level, especially in the West Sumatra region.